Recovery-stress balance in professional and U-21 soccer: differences between starters and substitutes - Filho, E.; Butterworth, K. (Sport Sciences for Health, 2021)
Soccer players at the U-21 level are in the challenging process of transitioning to the professional level. Accordingly, we examined whether U-21 soccer players would show a similar recovery-stress balance profile as professional soccer players. Furthermore, we explored differences in recovery-stress balance by playing status (i.e., starter or substitute). Twenty-nine players from a League One (UK) soccer club (15 professional players and 14 U-21 players) participated in the study. The players completed a demographic form and the Recovery-Stress Questionnaire for Athletes (RESTQ-Sport). A series of 2 (team: professional or U-21) × 2 (player status: starter or substitute) ANOVAs were performed on all sub-dimensions of the RESTQ-Sport. Starters showed significantly higher levels of general well-being, being in shape, and self-efficacy. Furthermore, analysis of the interaction terms suggested that players who were professional and substitutes showed the least healthy recovery-stress balance profile among all groups of players. Accordingly, coaches and applied sport psychologists should pay special attention to the recovery-stress balance of substitute players who might be at a higher risk of overtraining and burnout.